(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
The age of toddlers is 1-3 years, and this period is very decisive for children to get optimal growth and development. Language ability is an important aspect that shows the overall development of children. Language disorder is a problem that is often found in children. The impact of these disorders can be detrimental to the child’s development in the future. This study aims to analyze whether there is a relationship between knowledge and attitudes of mothers about early stimulation and language development in children aged 1-3 years at PAUD Nurul Huda, Grobogan Regency. This research is an analytic observational type with a cross sectional approach. The total sampling method was applied to obtain a sample of 30 respondents. Data were obtained from filling out questionnaires through interviews with mothers of students aged 1-3 years at PAUD Nurul Huda, and examination of language development using denver II. The chi-square test was used to analyze the data. The study’s results showed a significant relationship between mother’s knowledge and children’s language development (p=0.037) and a significant relationship between mother’s attitude and children’s language development (p=0.031). There is a significant relationship between mother’s knowledge and attitudes and the language development of children aged 1-3 years at PAUD Nurul Huda. In conclusion, the higher the level of mother’s knowledge and attitude, the better the child’s language development.